Recuperação de cobalto e de lítio de baterias íon-lítio usadas Recovery of cobalt and lithium fromspent Li-ion batteries - Natália Giovanini Busnardo; Jéssica Frontino Paulino; Julio Carlos Afonso (Química Nova, 2007)
The "active mass" (cathode + anode + electrolyte) of spent Li-ion batteries was submitted to one of the following procedures: (a) it was calcined (500 ºC) and submitted to extraction with water to recover lithium salts. The residual solid was treated with sulfuric acid containing hydrogen peroxide. Cobalt was recovered as sulfate; (b) the "active mass" was treated with potassium hydrogen sulfate (500 ºC) and dissolved in water. Cobalt was precipitated together with copper after addition of sodium hydroxide. Lithium was partially recovered as lithium fluoride. Co-processing of other battery components (aluminum and copper foils) affected negatively the behavior of the recovery procedures. Previous segregation of battery components is essential for an efficient and economical processing of the "active mass".